2003
DOI: 10.1161/01.hyp.0000042664.75193.1b
|View full text |Cite
|
Sign up to set email alerts
|

TA Repeat Variation, Npr1 Expression, and Blood Pressure

Abstract: Abstract-The activity of the atrial natriuretic peptide receptor (Npr1) is altered in spontaneously hypertensive rats (SHR) in relation to its mRNA levels, suggesting abnormal transcriptional control in hypertension. A single-stranded conformational polymorphism caused by a repetitive dinucleotide segment of 10 TA in BN-Lx and of 40 TA in SHR was localized at position Ϫ943 relative to the transcription start site of the Npr1 gene, downstream of a putative cGMP-regulatory region, and was the only sequence dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Earlier studies have demonstrated a significant association of Npr1 gene variants with hypertensive family history, left ventricular mass index, and left ventricular septal wall thickness in human essential hypertension (14,15). It has also been shown that a longer thymine adenine repeat unit in spontaneously hypertensive rats regulates the transcription of the Npr1 gene, thus affecting diastolic blood pressure (16). Little is known about transcriptional regulation of the Npr1 gene, but the activity and expression of NPRA, assessed primarily through ANP-stimulated cGMP accumulation, are mediated by factors, including auto-regulation involving natriuretic peptides and other hormones (17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Atrial Natriuretic Peptide (Anp)mentioning
confidence: 99%
“…Earlier studies have demonstrated a significant association of Npr1 gene variants with hypertensive family history, left ventricular mass index, and left ventricular septal wall thickness in human essential hypertension (14,15). It has also been shown that a longer thymine adenine repeat unit in spontaneously hypertensive rats regulates the transcription of the Npr1 gene, thus affecting diastolic blood pressure (16). Little is known about transcriptional regulation of the Npr1 gene, but the activity and expression of NPRA, assessed primarily through ANP-stimulated cGMP accumulation, are mediated by factors, including auto-regulation involving natriuretic peptides and other hormones (17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Atrial Natriuretic Peptide (Anp)mentioning
confidence: 99%
“…They found that 5′ flanking region haplotypes were associated with up to a 2-fold difference in reporter expression [34]. Interestingly, this parallels rat model data where a length-repeat variant in the promoter region correlated with gene expression as well as diastolic BPs [39]. Consistent with this line of evidence is a study in humans, which showed that a microsatellite polymorphism in the 5′ flanking region was associated with cardiac hypertrophy among hypertensive patients [40].…”
Section: Evidence Of Altered Biologic Function and Disease Risk Basedmentioning
confidence: 57%
“…The activity of NPRA, or NPR1 for its gene designation, is altered in spontaneously hypertensive rats (SHR) and a single-stranded conformational polymorphism in NPR1 gene has been recently described [66] ANP has been found to be raised in essential hypertension [67], in pheochromocytoma [68], and in obesity-associated hypertension [69]. A potential role of ANP system in blood pressure control has been supported by data coming from molecular genetic studies.…”
Section: Hypertensionmentioning
confidence: 99%